miR-208a in Cardiac Hypertrophy and Remodeling - Huang, Xing-Huai; Li, Jia-Lu; Li, Xin-Yue; Wang, Shu-Xia; Jiao, Zhi-Han; Li, Si-Qi; Liu, Jun; Ding, Jian (Frontiers in Cardiovascular Medicine, 2021)
Various stresses, including pressure overload and myocardial stretch, can trigger cardiac remodeling and result in heart diseases. The disorders are associated with high risk of morbidity and mortality and are among the major health problems in the world. MicroRNAs, a class of 22nt-long small noncoding RNAs, have been found to participate in regulating heart development and function. One of them, miR-208a, a cardiac-specific microRNA, plays key role(s) in modulating gene expression in the heart, and is involved in a broad array of processes in cardiac pathogenesis. Genetic deletion or pharmacological inhibition of miR-208a in rodents attenuated stress-induced cardiac hypertrophy and remodeling. Transgenic expression of miR-208a in the heart was sufficient to cause hypertrophic growth of cardiomyocytes. MiR-208a is also a key regulator of cardiac conduction system, either deletion or transgenic expression of miR-208a disturbed heart electrophysiology and could induce arrhythmias. In addition, miR-208a appeared to assist in regulating the expression of fast- and slow-twitch myofiber genes in the heart. Notably, this heart-specific miRNA could also modulate the “endocrine” function of cardiac muscle and govern the systemic energy homeostasis in the whole body. Despite of the critical roles, the underlying regulatory networks involving miR-208a are still elusive. Here, we summarize the progress made in understanding the function and mechanisms of this important miRNA in the heart, and propose several topics to be resolved as well as the hypothetical answers. We speculate that miR-208a may play diverse and even opposite roles by being involved in distinct molecular networks depending on the contexts. A deeper understanding of the precise mechanisms of its action under the conditions of cardiac homeostasis and diseases is needed. The clinical implications of miR-208a are also discussed.